2021
DOI: 10.20473/ijtid.v9i3.29113
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent Plasma Therapy: The Early Use in Moderate to Severe COVID-19 Patients in Hospitals with Limited Resources

Abstract: COVID-19 cases in Indonesia in the period of June-July 2021 showed a catastrophic spike. During this period, a recently discovered variant, the delta variant, appeared to be one of the sources of COVID-19 infection. Treatment modalities are limited due to reduced stock of drugs. A case of a 63-year-old man has been reported, with a history of having been vaccinated with two doses of Sinovac, experiencing moderate-to-severe symptoms of COVID-19 infection then given convalescent plasma therapy since his initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Rejeki et al [24] showed that patients with moderate symptoms of COVID-19 had significant clinical improvement after CCP. Another case report by Mahdi et al [25] described the patient given CCP for 3 days in a row as replacement therapy. This is because Favipiravir shortages showed improvement in symptoms such as shortness of breath, fever, and weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Rejeki et al [24] showed that patients with moderate symptoms of COVID-19 had significant clinical improvement after CCP. Another case report by Mahdi et al [25] described the patient given CCP for 3 days in a row as replacement therapy. This is because Favipiravir shortages showed improvement in symptoms such as shortness of breath, fever, and weakness.…”
Section: Discussionmentioning
confidence: 99%